Stress and burnout : a growing problem for non-manual workers (Washington, DC, 2002)
"Everybody knows what stress is all about. It is part of life and perhaps, to some extent, necessary at work and outside work. Some people are even more productive and creative when they work under stress. But if stress is intense and continuous, then it becomes a negative phenomenon leading to physical illness and psychological disorders. The European Union has done some valuable research work on stress which shows that there seems to be differences between north and south. Whereas the labour force in southern Europe reports more extensive problems in the physical and ergonomic work environment, the countries in northern Europe report far higher stress levels. How can unions increase member awareness and knowledge regarding the causes of occupational stress and its impact on health? How do they respond to it? ..."